FUZZY LOGIC UNTUK MENENTUKAN PENJUALAN RUMAH DENGAN METODE MAMDANI (STUDI KASUS: PT GRACIA HERALD) - sunarsan sitohang (Journal Information System Development, 2017)
The house is one of the basic needs for human beings. Along with the growth in population, housing needs increase. This is evidenced by the proliferation of complex construction of housing, especially in big cities are densely populated as the city of Batam. However, during PT Gracia Herald stands, the company is very difficult to see an increase or decrease in home sales per month of annual data, Fuzzy Logic to determine home sales methods mamdani is one method that can be applied both in the field determine home sales in PT Gracia Herald, Data collection techniques used by investigators are interviewing techniques, documentation studies, and literature. Steps being taken in this study started from processing of data per month in each year, the establishment of fuzzy set, forming a fuzzy rules, fuzzy inference models, assertion (defuzzification). Testing the system uses existing home sales data out of the twelve months in a year, defining the membership function in this study using triangular and trapezoidal curve with rule number seventy-nine rules. The result in April, June and November are sales rose.  Keywords: Home Sales, Fuzzy Logic, Mamdani Methods, MATLAB.